Automatic ictal onset source localization in presurgical epilepsy evaluation. Issue 6 (June 2018) - Koren, Johannes; Gritsch, Gerhard; Pirker, Susanne; Herta, Johannes; Perko, Hannes; Kluge, Tilmann; Baumgartner, Christoph
Highlights: Ictal onset source localization (IOSL) showed high diagnostic accuracy during presurgical evaluation. IOSL contributes to a correct localization of the seizure onset zone on a sublobar level. IOSL can be obtained within 5 minutes per seizure and used in standard epilepsy monitoring settings. Abstract: Objective: To test the diagnostic accuracy of a new automatic algorithm for ictal onset source localization (IOSL) during routine presurgical epilepsy evaluation following STARD (Standards for Reporting of Diagnostic Accuracy) criteria. Methods: We included 28 consecutive patients with refractory focal epilepsy (25 patients with temporal lobe epilepsy (TLE) and 3 with extratemporal epilepsy) who underwent resective epilepsy surgery. Ictal EEG patterns were analyzed with a novel automatic IOSL algorithm. IOSL source localizations on a sublobar level were validated by comparison with actual resection sites and seizure free outcome 2 years after surgery. Results: Sensitivity of IOSL was 92.3% (TLE: 92.3%); specificity 60% (TLE: 50%); positive predictive value 66.7% (TLE: 66.7%); and negative predictive value 90% (TLE: 85.7%). The likelihood ratio was more than ten times higher for concordant IOSL results as compared to discordant results ( p  = 0.013). Conclusions: We demonstrated the clinical feasibility of our IOSL approach yielding reasonable high performance measures on a sublobar level. Significance: Our IOSL method may contribute to a correct localization of the seizure onset zone in temporal lobe epilepsy and can readily be used in standard epilepsy monitoring settings. Further studies are needed for validation in extratemporal epilepsy.